LEADERSHIP COLLABORATION AND PROFESSIONAL ETHICS BETWEEN TEACHERS - Hosaini; Zainuddin; Abdul Halim; Muhamad Risal Tawil; Ifadhila (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Applying teacher leadership in the learning process is crucial in the classroom since it can greatly increase student learning achievement. To become a professional teacher, you must have professional education ethics in carrying out the educational process both at school, at home and in the community. The ongoing education process must adhere to the ethics, morals and etiquette that develop in society so that the education process can run in accordance with national education goals. The purpose of this writing is to describe teacher leadership and professional ethics. In this writing the method used is the literature study method. The conclusion of this research is that learning leadership and professional ethics can improve teacher teaching performance. Effective quality education must formulate and articulate learning objectives, guide development, improvement and learning processes, evaluate teacher performance and develop it, and develop learning programs that can meet needs.